Polysulfide Na2S4 regulates the activation of PTEN/Akt/CREB signaling and cytotoxicity mediated by 1,4-naphthoquinone through formation of sulfur adducts - Yumi Abiko (Nature Portfolio, 2017)
Abstract Electrophiles can activate redox signal transduction pathways, through actions of effector molecules (e.g., kinases and transcription factors) and sensor proteins with low pKa thiols that are covalently modified. In this study, we investigated whether 1,4-naphthoquinone (1,4-NQ) could affect the phosphatase and tensin homolog (PTEN)–Akt signaling pathway and persulfides/polysulfides could modulate this adaptive response. Simultaneous exposure of primary mouse hepatocytes to Na2S4 and 1,4-NQ markedly decreased 1,4-NQ-mediated cell death and S-arylation of cellular proteins. Modification of cellular PTEN during exposure to 1,4-NQ was also blocked in the presence of Na2S4. 1,4-NQ, at up to 10 µM, increased phosphorylation of Akt and cAMP response element binding protein (CREB). However, at higher concentrations, 1,4-NQ inhibited phosphorylation of both proteins. These bell-shaped dose curves for Akt and CREB activation were right-shifted in cells treated with both 1,4-NQ and Na2S4. Incubation of 1,4-NQ with Na2S4 resulted in formation of 1,4-NQ–S–1,4-NQ-OH. Unlike 1,4-NQ, authentic 1,4-NQ-S-1,4-NQ-OH adduct had no cytotoxicity, covalent binding capability nor ability to activate PTEN-Akt signaling in cells. Our results suggested that polysulfides, such as Na2S4, can increase the threshold of 1,4-NQ for activating PTEN–Akt signaling and cytotoxicity by capturing this electrophile to form its sulfur adducts.